2013
DOI: 10.2741/s361
|View full text |Cite
|
Sign up to set email alerts
|

Current status of human pluripotent stem cell based in vitro toxicity tests

Abstract: The present review assesses the current status of in vitro tests based on human pluripotent stem cell-derived toxicologically relevant target cells. The majority of the evaluated test systems are in the phase of test development. In particular the success rates of differentiation protocols and their reproducibility are varying depending on different culture conditions but also on the assessed marker panel and the functional evaluation of the cells. However, the amount of differentiated cells decreases in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The currently available test systems have been characterized by the use of well-known positive control compounds, which mainly belong to the group of environmental toxicants (Klaric et al 2013; Vojnits et al 2012; Krug et al 2013a; Pallocca et al 2013; Laurenza et al 2013; Piersma et al 2013; Bal-Price et al 2012; Crofton et al 2011; Coecke et al 2007; Lein et al 2007; Kadereit et al 2012). Some others have used at most one to three drug-like compounds (Balmer et al 2012; Stiegler et al 2011; Kuegler et al 2012; Meganathan et al 2012; Jagtap et al 2011; Falsig et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The currently available test systems have been characterized by the use of well-known positive control compounds, which mainly belong to the group of environmental toxicants (Klaric et al 2013; Vojnits et al 2012; Krug et al 2013a; Pallocca et al 2013; Laurenza et al 2013; Piersma et al 2013; Bal-Price et al 2012; Crofton et al 2011; Coecke et al 2007; Lein et al 2007; Kadereit et al 2012). Some others have used at most one to three drug-like compounds (Balmer et al 2012; Stiegler et al 2011; Kuegler et al 2012; Meganathan et al 2012; Jagtap et al 2011; Falsig et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The results of valproic acid of the present study are in good agreement with previous studies performed in neuronal precursor cells derived from human embryonic stem cells (Waldmann et al 2014). In this study, three types of impacts related to different concentration ranges have been defined: (1) a range of tolerance, observed valproic acid concentrations up to 25 μM, suggesting the existence a threshold mechanisms (Dietrich et al 2013); (2) a deregulated/teratogenic effect was observed at concentrations between 150 and 550 μM of valproic acid, which was associated with developmental disturbances, impaired cell migration, and the down-regulation of neuronal pathways (Balmer et al 2012; Klaric et al 2013); (3) a cytotoxic concentration range at 800 and 1000 μM.…”
Section: Resultsmentioning
confidence: 99%
“…This interest stems from the hypothesis that human hazard is probably best assessed in assays with human biological systems, which is one of the key messages from the NAS landmark report on toxicity testing in the 21st century [31]. In the past, primarily mESC were used for the stem cell test [32] which provided ground work for development of the EST [33].…”
Section: Embryonic Stem Cell Testsmentioning
confidence: 99%